2019
DOI: 10.1016/j.jval.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Estimators Used in Multisite Healthcare Costing Studies in Low- and Middle-Income Countries: A Systematic Review and Simulation Study

Abstract: BackgroundIn low- and middle-income countries, multisite costing studies are increasingly used to estimate healthcare program costs. These studies have employed a variety of estimators to summarize sample data and make inferences about overall program costs.ObjectiveWe conducted a systematic review and simulation study to describe these estimation methods and quantify their performance in terms of expected bias and variance.MethodsWe reviewed the published literature through January 2017 to identify multisite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…First, the studies we included in the analysis were heterogeneous in terms of the scope of costing, site selection, data collection methods, and the level of detail with which results were reported. This heterogeneity in costing study methods and reporting has been observed by prior reviews [51][52][53][54][55]. We attempted to deal with this by adopting an analytic strategy that allowed for differences in the cost categories and types of costs (i.e., financial vs. economic) reported.…”
Section: Discussionmentioning
confidence: 99%
“…First, the studies we included in the analysis were heterogeneous in terms of the scope of costing, site selection, data collection methods, and the level of detail with which results were reported. This heterogeneity in costing study methods and reporting has been observed by prior reviews [51][52][53][54][55]. We attempted to deal with this by adopting an analytic strategy that allowed for differences in the cost categories and types of costs (i.e., financial vs. economic) reported.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these data contribute to the understanding of how to improve planning and allocate existing resources to maximise value for money or efficiency. While large scale, multi-site cost data are generally required to capture the variability in costs and efficiency [ 12 ], information on HIV service costs in sub-Saharan Africa are limited [ 13 ]. Moreover, few analyses exist of how costs might change as the epidemic and corresponding care and treatment strategies evolve.…”
Section: Introductionmentioning
confidence: 99%
“…We also acknowledge the importance of careful consideration of the method used for performing an economic analysis. While the assumptions used in our study differ from others recently published [51,52], we believe that the assumptions behind our estimates are solid and our bias is somewhat controlled as we cite official public pricing. Finally, we realize that the use of estimated incidence rates reported by Centers for Disease Control and Prevention (United States of America) for indirect standardisation of incidence rates for Mexico may not be ideal; however, we thought this was necessary because the SISVEFLU database likely underestimates the number of cases from primary care clinics, lacks the necessary population representation and most type B influenza cases reported in the database do not have lineage analysis (Additional file 1: Supplement 1; Text S1.2).…”
Section: Discussionmentioning
confidence: 72%